Implementasi Konfigurasi Hotspot Di Kantor Desa Dengan Menggunakan Router Mikrotik Yang Terintegrasi Dengan Aplikasi Mikhmon - abdul rahman, Ujang (Universitas Majalengka, 2021)
Internet network management is absolutely necessary for agencies that use tools that require an Internet connection, such as PC computers, laptops, or smart phones, the increasing number and variety of applications that can be served by a network affects the use of links in the network. It has become a necessity that in today's era Wireless (Wifi Hotspot) is very much needed, both for laptop internet needs and, making it easier for patra users of these tools to use it as a support for their activities at work. Routers have a function to manage connections in a network, but without proper methods, techniques and configuration, the network will not function optimally. The Mikrotik router is an operating system that includes a full range of features for wireless networks. Mikrotik can also function as a firewall for the user's computer so that they can access internet data and local data. Mikrotik aims to regulate bandwidth and perform computer network management. Mikrotik router is placed as a gateway to a network. The gateway computer functions to distribute data in and out of and to other computers so that all computers can access data together such as Internet sharing (Mancill: Dua Thousand Dua). The problem that exists at the Cieurih Village Office is the inadequate use of the internet network to support the performance of village officials, so that internet usage at the office becomes inefficient because every user connected to the network can take advantage of the internet connection for personal needs. Currently, the Cieurih Village Office only uses Mikrotik Access Points from ISP Artha Flash and Switch Hub as internet network dividers and functions only to provide internet services without configuration from a router as described above so that the network received by every device connected to it The internal network at the Cieurih village office is unstable and very poorly supports the performance of village officials due to the absence of network management, not to mention devices that cannot use the internet via LAN cables such as Notebooks and SmartPhone which can only be connected to the internet network via Wireless (Wifi Hotspot) can not be used optimally.